The alternative approach: genomic classifiers for prognostication in interstitial lung disease. Issue 4 (3rd April 2023) - Goobie, Gillian C.; Guler, Sabina A.
Interstitial lung disease (ILD) reflects a large group of entities characterised by pulmonary parenchymal inflammation and fibrosis, with many patients suffering from functional limitation, progressive symptoms and accelerated mortality [1]. Idiopathic pulmonary fibrosis (IPF), which is characterised by a usual interstitial pneumonia (UIP) pattern on imaging and histology, is the most common and deadly form of ILD [2, 3]. Prognosis and treatment approaches differ between ILD subtypes, making an accurate diagnosis crucial; however, this can be challenging due to overlapping clinical and morphological presentations of some ILDs. The potential of genomic classifiers for ILD prognostication has not been exhausted yet http://bit.ly/3ZMMdjx